How do travelers manage jetlag and travel fatigue? A survey of passengers on long-haul flights. (1st November 2020) - Bin, Yu Sun; Ledger, Susan; Nour, Monica; Postnova, Svetlana; Stamatakis, Emmanuel; Cistulli, Peter A.; de Chazal, Philip; Allman-Farinelli, Margaret; Caillaud, Corinne; Bauman, Adrian; Simpson, Stephen J
ABSTRACT: Jetlag and travel fatigue can impair functioning, but it is unknown what strategies are used by travelers to minimize these consequences. Passengers on Qantas Airways flights were invited to take part in online surveys. Long-haul flights of ≥8 h into and out of Australia were targeted, which involved time differences of 1 to 18 h between the origin and destination. Passengers were queried about the use of travel booking choices before the flight, and the use of behavioral strategies before, during, and after flight for reducing jetlag and travel fatigue. Surveys were completed by N = 460 passengers aged 18 to 78 (43% male; mean age 50 y). Selecting a seat location (59%) and choosing a direct flight (52%) were the most common booking strategies. Almost all (99%) employed specific behavioral strategies during flight, with fewer implementing strategies before flight (73%) and after flight (89%). During the journey, 81% consumed or avoided caffeine and alcohol, 68% altered food intake, 68% used comfort/relaxation strategies, 53% light exposure, 35% physical activity, 31% compression stockings, 15% pharmaceutical sleep aids, and 8% melatonin. Surprisingly, only 1 of 460 passengers reported using a jetlag app. Younger travelers were more likely to adopt any strategy before the flight than older travelers (χ 2 2 = 14.90, p =.01), while female travelers appeared more likely than male travelers to use strategies before (77% vs. 68%) and after flight (91% vs. 85%). Reason for travel, flight cabin, leg of journey, and country of residence were not significantly associated with the use of behavioral strategies. Nearly all passengers took measures to improve the experience and consequences of long-haul flying. The results suggest that interventions around food/drink and physical activity may be highly acceptable to passengers for mitigating travel fatigue and that greater public education on evidence-based strategies may be helpful for reducing travel fatigue and jetlag.